Perlindungan Hukum terhadap Hak Anak dalam Proses Perceraian: Studi tentang Kepentingan Anak dalam Pengadilan Keluarga - Muhammad Firdaus (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2023)
Divorce is a complex social phenomenon that can have significant impacts on various aspects of life. Family courts play a central role in resolving divorce disputes and determining child custody arrangements. This study aims to thoroughly examine how legal protection for children's rights is upheld during the divorce process in family courts. The analysis will be conducted by understanding the legal aspects related to children's rights, including custody, financial support, education, and general protection. The research methodology employed is a qualitative approach, with a case study approach as the main design. The qualitative approach was chosen to provide an in-depth understanding of the perspectives and experiences of various parties involved in the family justice process, including parents, children, and legal professionals. Data collection will be conducted through several stages. First, in-depth interviews will be conducted with parents involved in divorce cases, while ensuring the child's perspective is also obtained through the use of specialized child interview methods. The results of this research reveal a variety of cases in the divorce process brought before family courts. These cases involve diverse issues related to children's rights, such as custody, financial support, and communication access with non-custodial parents. In some cases, the interests of the child are neglected or not fully considered, while in other cases, family courts have made efforts to carefully preserve and protect children's rights